Validation of the revised Compound PsyCap Scale (CPC-12R) and its measurement invariance across the US and Germany - Lorenz, Timo; Hagitte, Leonie; Prasath, Priscilla Rose (Frontiers in Psychology, 2022)
The purpose of this study was to validate the English and German versions of the revised Compound PsyCap Scale (CPC-12R) in a US-sample (n = 385) and a sample from Germany (n = 202). The twelve-item CPC-12R exhibited the anticipated factorial structure with an excellent model fit in both samples and associations to other constructs concurred with previous findings. A specific aim was to examine the measurement invariance of the CPC-12R across the two countries. Scalar measurement invariance was established. Overall, these findings suggest that the CPC-12R is an economic, valid, reliable and applicable tool in the US and Germany to assess psychological capital (PsyCap). The scalar measurement invariance highlights the importance of taking cultural background and possible pitfalls for cross-cultural research into account for future PsyCap research.